Clinical trials involving cats: What factors affect owner participation?. Issue 9 (September 2014) - Gruen, Margaret E; Jiamachello, Katrina N; Thomson, Andrea; Lascelles, B Duncan X
Study rationale: Clinical trials are frequently hindered by difficulties in recruiting eligible participants, increasing the timeline and limiting generalizability of results. In veterinary medicine, where proxy enrollment is required, no studies have detailed what factors influence owner participation in clinical trials involving cats. We aimed to investigate these factors through a survey of owners at first opinion practices. Protocol: The survey was designed using feedback from a pilot study and input from clinical researchers. Owners were asked demographic questions and whether they would, would not, or were unsure about participating in a clinical trial with their cat. They then ranked the importance and influence of various factors on participation using a five-point Likert-type scale, and incentives from most to least encouraging. A total of 413 surveys were distributed to cat owners at four hospitals, two feline-only and two multi-species; 88.6% were completed. Data for importance and influence factors as well as incentive rankings were analyzed overall, and by hospital type, location and whether owners would consider participating. Findings: The most influential factors were trust in the organization, benefit to the cat and veterinarian recommendation. Importance and influence factors varied by willingness to participate. Ranked incentives were not significantly different across groups, with 'Free Services' ranked highest. Relevance: This study provides a first look at what factors influence participation in clinical trials with cats. Given the importance placed in the recommendation of veterinarians, continued work is needed to determine veterinarian-related factors affecting clinical trial participation. The results provide guidance towards improved clinical trial design, promotion and education.